Effect Of Long-Term Use Of Antithrombotics And Statins On COVID-19 Mortality And Clinical Severity - Murat Özmen; Faruk Aydınyılmaz; Selim Aydemir; Emrah Aksakal (Atatürk University, 2024)
Objective: Coronavirus Disease-2019 (COVID-19), has affected the whole world and is still an important disease with its mutations. In our study, we aimed to evaluate the effects of antithrombotic agents [acetylsalicylic acid (ASA), P2Y12 inhibitors, oral anticoagulants (OACs)] and statin treatments used before hospitalization on COVID-19 mortality and clinical severity.Methods: A retrospective study was conducted on 5577 patients hospitalized with positive swab tests or findings consistent with COVID-19 on computed tomography. The 6-month mortality, in-hospital mortality, need for intensive care and intubation, and recurrent hospitalization outcomes of patients receiving chronic ASA (n=1210), P2Y12 inhibitors (n=357), OACs (n=1192), and statin (n=607) treatment were evaluated.Results: The 6-month mortality rate was 13.5% (n=754), in-hospital mortality rate was 11.2% (n=627), the rate of admission to the intensive care unit was 16.1% (n=897), the need for intubation was 8.8% (n=493), and the rate of recurrent hospitalization was 10.4% (n=579). ASA and OACs reduced all outcomes. P2Y12 inhibitors provided benefit in other endpoints except intubation. Statins used before hospitalization did not provide a statistically significant decrease in 6-month mortality (p: 0.06), but were associated with a decrease in the rates of in-hospital mortality, need for intensive care, recurrent hospitalization, and intubation. Conclusion: We found that long-term ASA, P2Y12 inhibitors, OACs and statin treatments used before hospitalization in patients hospitalized with COVID-19, reduced COVID-19 mortality and clinical severity. We think that these treatments may be beneficial in selected patient groups where post-COVID effects are observed.